Abundance and diversity of sedimentary bacterial communities in a coastal productive setting in the Western Irish Sea. (1st February 2016) - O'Reilly, S.S.; Pentlavalli, P.; Flanagan, P.V.; Allen, C.C.R.; Monteys, X.; Szpak, M.T.; Murphy, B.T.; Jordan, S.F.; Kelleher, B.P.
Abstract: The bacterial community composition and biomass abundance from a depositional mud belt in the western Irish Sea and regional sands were investigated by phospholipid ester-linked fatty acid profiling, denaturing gradient gel electrophoresis and barcoded pyrosequencing of 16S rRNA genes. The study area varied by water depth (12–111 m), organic carbon content (0.09–1.57% TOC), grain size, hydrographic regime (well-mixed vs. stratified), and water column phytodetrital input (represented by algal polyunsaturated PLFA). The relative abundance of bacterial-derived PLFA (sum of methyl-branched, cyclopropyl and odd-carbon number PLFA) was positively correlated with fine-grained sediment, and was highest in the depositional mud belt. A strong association between bacterial biomass and eukaryote primary production was suggested based on observed positive correlations with total nitrogen and algal polyunsaturated fatty acids. In addition, 16S rRNA genes affiliated to the classes Clostridia and Flavobacteria represented a major proportion of total 16S rRNA gene sequences. This suggests that benthic bacterial communities are also important degraders of phytodetrital organic matter and closely coupled to water column productivity in the western Irish Sea. Highlights: Sedimentary bacterial communities investigated in shallow, shelf setting in Irish Sea. Biomass abundance, as bacterial-derived fatty acids, was higher in the mud belt region. 16S rDNA sequences for Clostridia, Flavobacteria and Proteobacteria dominated. Bacteria coupled to primary production as degraders of phytodetritus. Hydrographic and depositional conditions likely influence sedimentary bacteria.